PERAN KEPEMIMPINAN KEPALA MADRASAH DALAM MENGEMBANGKAN BUDAYA MEMBACA AL-QUR’AN DI MADRASAH TSANAWIYAH NEGERI 1 PALEMBANG - Erna Wati (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2017)
This background of the effort to improve the learning process of the Qur'an is necessary because the Qur'an is the source of the law and the main rule for Muslims and grace performed MTs N 1 Palembang. The purpose of this research is to know and understand the role of leadership of madrasah head in developing the culture of reading al-Qur'an in MTs Negeri 1 Palembang and the impact of leadership role of madrasah head in developing the culture of reading al-Qur'an in MTs Negeri 1 Palembang. The research results obtained the following results: The role of leadership of madrasah head in developing the culture of reading the Qur'an in MTs Negeri 1 Palembang seen in the ability to coordinate the activities tahfidz al-Qur'an, in terms of problem solving in the program of culture al-Qur 'An, he gave authority to the concerned to solve it. The principal establishes communication with good language especially on issues in which the cultural activities of reading the Qur'an are concerned. The principal has given good motivation to the participants tahfidz the teacher in charge, both in the form of praise, trust and physical form. The impact of the leadership role of madrasah head in developing the culture of reading al-Qur'an in MTs Negeri 1 Palembang make the program of reading al-Qur'an culture focused on the activities of tahfidz al-Qur'an in MTs N 1 Palembang run effectively proven by many students Already memorized 1 juz even have 5 and 7 juz.